Cavitation loading and erosion produced by a cavitating jet - Momma, Takahiro (1991)
The aim of the project is to investigate the detail of cavitation loading and erosion process using a submerged jet cavitation technique. Large size cavitating jet apparatus in the University of Nottingham was used with an long orifice nozzle and experiments were carried out using tap water as a test liquid with upstream pressure ranging from 8D-120bar.